Role of Ambassadors in Development Diplomacy in the Context of Nepal - Karki, Nir Bahadur (NCWA Annual Journal, 2023)
Diplomacy has existed for a long time as an integral component of maintaining relations with other countries as required by factors like geopolitical aspects, international situation, population size, the economy's productivity, security sensitiveness, military strength, and main law of the land. Diplomacy is a vital tool for implementing foreign policy construed as an art of dealing with the diplomats of other countries for the host country’s benefit. The style and manner of diplomacy are shifting with time in the form of expanding the sphere of influence by the stronger power over the weaker power, economic domination, marine power, and navigational supremacy. The Ministry of Foreign Affairs, led by the foreign minister, ministry staff, and ambassadors abroad constitute the key actors in executing development diplomacy. Nepal has failed to grasp the opportunity due to her inability to select skillful candidates for such fascinating but challenging roles at various times compared to the past. Development diplomacy constitutes a significant part of overall diplomacy for most of the developing countries as is the case of Nepal with a major thrust of receiving development cooperation as much as possible from the advanced countries in the form of grants as well as loans with the minimum possible rate of interest.